Study of stereochemical effect of galactoside mixture based on reaction time / Nurul Fadhilah Kamalul Aripin, Mohamad Iqbal Ab Doroh and Marina Yusoff - Kamalul Aripin, Nurul Fadhilah; Ab Doroh, Mohamad Iqbal; Yusoff, Marina Yusoff (Universiti Teknologi MARA Shah Alam, 2018)
Synthesis of palm kernel oil-based galactoside involves a three-step process: acetylation, glycosylation and deacetylation. Glycosylation reaction produced two stereoisomeric galactosides: α-anomer and β-anomer. The quantity of these anomers is directly dependent on the glycosylation time as each anomer is either kinetically or thermodynamically favoured. In this work, we studied the effect of time towards the production of predominating anomers. The quantity of the anomers is reported in terms of α/β ratio based on the integration of proton NMR peaks of the final product. From the result, it is found that the quantity of α-anomer increased by average of 1.15 %/h